Container Ocean-transportation System Design with the factors of demand fluctuation and choice inertia of shippers. (November 2016) - Chen, Kang; Chen, Dongxu; Sun, Xueshan; Yang, Zhongzhen
Highlights: We study a container shipping network design problem with network adjustment and shippers' choice inertia. This proposed problem is formulated as a bi-level programming model. An efficient heuristic optimization algorithm is proposed. Abstract: This paper introduces an optimization model (COSDM) for a Container Ocean-transportation System with the objective of maximizing the revenue of a liner company while taking into account the seasonal fluctuation in transportation demand and the choice inertia of shippers. The COSDM optimizes shipping network design and fleet deployment simultaneously, and it optimizes plans for changing the shipping network and for distributing slots in ships based on the fluctuation in demand and the characteristics of the shippers' choice inertia. To solve COSDM, a heuristic algorithm is created that combines Genetic Algorithm and Simplex Method. The results show that the COSDM gives an optimized design scheme of the system that takes into account the stability of transportation services and improves the user experience of shippers while increasing the revenue of the liner company. Moreover, the results also reveal new explanations for the increasing size of container ships.